Pemanfaatan Aplikasi Gobiz dan Grab Merchant untuk Meningkatkan Pendapatan UMKM Dimasa Pandemik Covid19 - Parameswari, Rinintha; Silaswara, Diana; Ginny, Puti Lenggo; Kusnawan, Agus; Anggraeni, Rr Dian (LP3kM Universitas Buddhi Dharma, 2022)
This activity explains the convenience of the applications and motivates the community of MSME actors in Teluk Naga, Tangerang, to use the applications offered by GoJek and Grab. The purpose of this training is to increase the income of MSME actors during the pandemic because the application can increase their income. After all, it is much easier to reach consumers. In this training, we used the on-the-spot method, the method of observation, discussion, and the trainer's experience and current conditions. These methods of the discussions, the question and the answer, as well as the provision of materials and practices to improve business planning management, online marketing management (E-Commerce). Several participants are also asked to explain the results of their business plans. It is hoped that the results of the evaluation of the 25 training participants, in general, can increase the knowledge, understanding and income of MSME actors in Teluk Naga Village, Tangerang.